2015
DOI: 10.1074/jbc.m115.662726
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Catalytic Mechanism of Copper Amine Oxidase from Arthrobacter globiformis with Halide Ions

Abstract: Background:Copper amine oxidases catalyze amine oxidation using copper and a quinone cofactor. Results: Halides bind axially to the copper center, preventing the reduced cofactor from adopting an on-copper conformation. Conclusion:The cofactor undergoes large conformational changes during the catalytic reaction that enable transitions between different types of chemistry. Significance: Molecular details of cofactor movement have been unveiled based on structural and kinetic evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
85
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(95 citation statements)
references
References 65 publications
(111 reference statements)
8
85
2
Order By: Relevance
“…7 and 8 in ref. 8), those determined at four different noncryogenic temperatures clearly showed a mixture of the two conformers (off-copper TPQ amr and on-copper TPQ sq ) in the F o -F c omit maps for residue 382 (TPQ; Fig. 2A).…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…7 and 8 in ref. 8), those determined at four different noncryogenic temperatures clearly showed a mixture of the two conformers (off-copper TPQ amr and on-copper TPQ sq ) in the F o -F c omit maps for residue 382 (TPQ; Fig. 2A).…”
Section: Resultsmentioning
confidence: 87%
“…Our previous study with AGAO crystals anaerobically reduced with a high-affinity substrate, 2phenylethylamine (2-PEA; K m = 2.5 μM) (4, 6), revealed that the oxidized product, phenylacetaldehyde (PAA), remains bound in the hydrophobic pocket close to TPQ, which could affect the TPQ sq /TPQ amr equilibrium (8). Therefore, we here used a lowaffinity substrate, ethylamine (K m = 170 mM) (6), as a reducing substrate, expecting that its oxidation product (acetaldehyde) is not bound to the pocket (8), and hence would not affect the TPQ sq /TPQ amr equilibrium to be investigated by X-ray crystallography, using the temperature-controlled HAG method. Diffraction data were obtained with multiple crystals selected arbitrarily from those formed in the same soaking conditions except for the temperature (4, 10, 15, and 20°C) (SI Appendix, Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations